2012
DOI: 10.1590/s1983-51752012000300030
|View full text |Cite
|
Sign up to set email alerts
|

Quebra de ponta de cânula, no plano gorduroso, durante lipoaspiração

Abstract: Wolfenson M et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…It is a rare complication and only two such cases have been reported in English literature. 3,4 Wolfenson et al reported a similar case with broken cannula tip in the left side of the chest 3 and Herbst and Saltvig reported broken cannula in the right thigh during liposuction. 4 In above both cases, the retained cannula tip was identified with C-arm and the broken tips were retrieved.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…It is a rare complication and only two such cases have been reported in English literature. 3,4 Wolfenson et al reported a similar case with broken cannula tip in the left side of the chest 3 and Herbst and Saltvig reported broken cannula in the right thigh during liposuction. 4 In above both cases, the retained cannula tip was identified with C-arm and the broken tips were retrieved.…”
mentioning
confidence: 98%
“…Wolfenson et al case report describes the cause for breakage is use of larger diameter cannulas more than 4 mm, which probably had defects, as narrow openings in the form of "slots," in the region of the lumen that, because they were in the interior of the cannula, were not detected by either the manufacturer's quality control evaluation or the medical team. 3 Herbst and Saltvig case report describes the causes for breakage to be as follows: cannulas used for infiltration are long, with thin walls and have several holes. These three elements make the cannula potentially at risk of damage or breakage.…”
mentioning
confidence: 99%
See 1 more Smart Citation